Characteristics of surge-type tributary glaciers, Karakoram - Bhambri, Rakesh; Hewitt, Kenneth; Haritashya, Umesh K.; Chand, Pritam; Kumar, Amit; Verma, Akshaya; Tiwari, Sameer Kumar; Rai, Santosh Kumar (Geomorphology, 2022)
The Karakoram has a large concentration of surge-type glaciers, including 69 tributary glaciers, compared to 152 surge-type main or trunk glaciers. The paper addresses the interactions between tributary and trunk glaciers using digital elevation models (DEMs), surface displacement, field and archival reports. In particular, it explores the behavior and impacts of 13 tributary glacier surges on three trunk glaciers, namely the Hispar, Braldu and Panmah. Observations include five surge tributaries of Panmah, five of Braldu, and three of Hispar. We observed ASTER DEMs can help in some cases to detect surge signature where automated surface displacement does not detect the surge. We also observed substantial differences in surge dimensions, timing and histories of the main trunk glacier and their tributaries. East Braldu III tributary surged between 2000 and 2003, whereas East Braldu IV surged from 2003 to 2006, but in these periods, no other tributary shows surge signature. Between 2013 and 2016, Braldu trunk Glacier surged along with four tributaries out of five except West Braldu I. Volumes and geometry of ice transferred from tributary to trunk glaciers are unique to each case, but the surging ice melted rapidly in about 2 to 4 years for some cases such as Little Skamri and Drenmang. The tributary ice modified all studied trunk glacier dynamics, morphology, distribution of debris and hypsography. The ice transferred from tributaries such as Little Skamri and Drenmang blocked the flow of trunk Nobande Sobonde Glacier from 2004 to 2006. Such ice transfer by surge tributaries to the main trunk glacier is referred here as surge-modified ice. It introduces indirect and post-surge effects and complicates or delay in tracking glacier responses to climate change. Also, mass balance in surge-type and surge-modified glaciers differ from systematic direct responses to climate in non-surge-type glaciers. Therefore, more research and monitoring are required to address the distinct responses of such glaciers and individual tributaries to better understand the heterogeneity of surging glaciers in Karakoram.